Involvement of the Antennal and Maxillary Palp Structures in Detection and Response to Methyl Eugenol by Male Bactrocera dorsalis (Diptera: Tephritidae). Issue 5 (22nd October 2018) - Chieng, Anna Chui-Ting; Hee, Alvin Kah-Wei; Wee, Suk-Ling
Abstract: The oriental fruit fly, Bactrocera dorsalis (Handel) is one of the most destructive pests of fruits. The discovery of methyl eugenol (ME) as a potent male attractant for this species has led to its successful use in area-wide fruit fly control programs such as male annihilation. While the antenna is recognized as primarily responsible for male flies' detection of attractants such as ME, little is known of the involvement of the maxillary palp. Using behavioral assays involving males with intact and ablated antennae and maxillary palp structures, we seek to ascertain the relative involvement of the maxillary palp in the ability of the male fly to detect ME. In cage bioassays (distance of ≤40 cm from the source), >97% of unmodified males will normally show a response to ME. Here, we showed that 17.6% of males with their antennae ablated were still attracted to ME versus 75.0% of males with their palps ablated. However, none of the antennae-ablated males were able to detect ME over a distance of >100 cm. Furthermore, wind tunnel bioassays showed that maxillary palp-ablated males took a significantly longer time compared to unablated males to successfully detect and eventually feed on ME. These results suggest that although the antennae are necessary for detection of ME over longer distances, at shorter distances, both antennae and maxillary palps are also involved in detecting ME. Hence, those palps may play a larger role than previously recognized in maneuvering males toward lure sources over shorter ranges.